2014
DOI: 10.1189/jlb.2a0913-487r
|View full text |Cite
|
Sign up to set email alerts
|

The TLR signaling adaptor TRAM interacts with TRAF6 to mediate activation of the inflammatory response by TLR4

Abstract: TLRs act as sentinels in professional immune cells to detect and initiate the innate immune response to pathogen challenge. TLR4 is a widely expressed TLR, responsible for initiating potent immune responses to LPS. TRAM acts to bridge TLR4 with TRIF, orchestrating the inflammatory response to pathogen challenge. We have identified a putative TRAF6-binding motif in TRAM that could mediate a novel signaling function for TRAM in TLR4 signaling. TRAM and TRAF6 association was confirmed by immunoprecipitation of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…The results of the present study demonstrated that exposure to 20 mg/kg LPS increased the expression levels of TLR4 in mice colon tissue. These results support the hypothesis that LPS activates the TLR4 signaling pathway, which in turn regulates the inflammatory response (23). Conversely, the expression levels of TLR4 in the colon of LPS-treated mice were inhibited by rhein and TAK-242.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results of the present study demonstrated that exposure to 20 mg/kg LPS increased the expression levels of TLR4 in mice colon tissue. These results support the hypothesis that LPS activates the TLR4 signaling pathway, which in turn regulates the inflammatory response (23). Conversely, the expression levels of TLR4 in the colon of LPS-treated mice were inhibited by rhein and TAK-242.…”
Section: Discussionsupporting
confidence: 78%
“…The LPS-induced overexpression of TLR4 is associated with changes in the levels of inflammatory mediators. Accumulating evidence has suggested that LPS-induced overactivation of the TLR4 signaling pathway leads to an increase in the production of pro-inflammatory mediators, with fatal consequences to the host (21)(22)(23). The results of the present study demonstrated that exposure to 20 mg/kg LPS increased the expression levels of TLR4 in mice colon tissue.…”
Section: Discussionsupporting
confidence: 65%
“…Given the bridging action between TLR 4 and TRIF, TICAM-2 coordinates the inflammatory response to a pathogen challenge [ 33 ]. Thus, it is easy to postulate that IR-induced aberrant TICAM-2 expression might be closely associated with TLR 4 activation, subsequent NF-κB relocation to the nucleus, and the release of downstream proinflammatory cytokines [ 9 , 32 , 34 ]. Consistent with this, here, we observe that TLR 4 expression is also significantly upregulated when TICAM-2 expression increased and miR-27a decreased at both 24 and 72 hours after IR (Figure 4 a, b, c, d, e).…”
Section: Discussionmentioning
confidence: 99%
“…TRAF6 represents a major point of bifurcation of TLR signalling between canonical and non-canonical induction of inflammation. Structural analysis of TRAF6-binding partners show a conserved binding motif consisting of Pro-X-Glu-X-X-(aromatic or acidic residue) 19 , required for interaction with downstream signalling proteins including Mal/TIRAP, TRIF, TRAM and STAT1 20,21,22,23 . Given the homology between STAT proteins and the role for STAT3 in mitochondrial reprogramming, we identified highly conserved putative TRAF6-binding motifs within STAT3 ( Fig.1a) and confirmed that the interaction between endogenous TRAF6 and STAT3 occurs within 10 minutes of LPS-stimulation in macrophages ( Fig.…”
Section: Resultsmentioning
confidence: 99%